The EU's Energy Roadmap 2050: Targets without governance - Oliver Geden; Severin Fischer (Stiftung Wissenschaft und Politik (SWP), 2012)
With the Energy Roadmap 2050 of December 2011, the European Commission has opened the debate about the future shape of Europe's energy sector. But two central conflicts within the Union narrow the relevance of this planning instrument in the ongoing political process. Firstly, the European consensus that climate policy should determine energy policy, which has held since 2007, is likely to erode. Secondly, formulating European targets for 2050 suggests a greater scope of governance than the EU actually possesses, mainly because the European treaties still reserve the decisive role in shaping the energy mix for the member states. If the governments of the EU member states take the long-term approach of a European energy roadmap seriously, they would have to accept a major curtailment of their national sovereignty over energy policy
Keywords: 320